PENGARUH VOLUME PERGANTIAN AIR MEDIA TERHADAP KELULUSHIDUPAN LARVA IKAN LELE SANGKURIANG (CLARIAS GARIEPINUS) - Umbu Rasa P. H.; Felix Rebhung; Ismawan Tallo (Nusa Cendana University, 2018)
Abstract - This research was conducted at the Laboratory of Fisheries and Marine Science Faculty of Nusa Cendana University, which aimed to find out the effect from difference volume substitution of water media on the survival rate of sangkuriang catfish larvae (Clarias gariepinus). The method used complete randomized design of with three treatments of water volume substitution that was A (25%), B (50%), C (75%) and control with three replications. The data were analyzed with variance (ANOVA) and continued with least significance different (BNT) test. The results showed that the water volume substitution of 25% had a significant effect on the survival rate of the larvae with 63.333% of survival rate. Keywords : Sangkuriang Catfish Larva, Substitution of Water Volume, Survival Rate, (Clariasgariepinus)